Projeto de um sistema de gancheira tipo transportador aéreo para uso em baús frigoríficos - Grotto, André Carlos (2021)
Road transport is the predominant means of moving products in Brazil. For the transport of chilled and/or frozen beef, refrigerated trunks of the hook model are used. These chests have a transverse structure and are fixed to the ceiling, where the meat is attached to this structure by hooks. The main problems found in these chests are the difficulty in loading, unloading and moving the meat inside. To solve this problem, the present work aims to develop a project for an air carrier type hook system, to be installed in refrigerated trunks that transport beef, replacing conventional methods and facilitating the task. For the development of the product, a project methodology consisting of four phases was used: project specification, conceptual project, preliminary project and detailed project. Used sequentially, the methodology provides organization and assistance in the preparation of the project and functional dimensioning of the air carrier type hook system. In the design phase, structural analyzes were used using the finite element method of static and fatigue type. Then, a structural analysis of the refrigerated trunk is presented, in order to simulate similar rolling conditions and evaluate the behavior of the structure with the new hook system. This evaluation is important for product validation, since the air transport developed impacts the structural analysis of the chest because the load distribution takes place differently than traditional hooks. In the analysis of the refrigerated truck, static, fatigue and dynamic analysis were performed. The results, from a structural point of view, show that the air carrier supports the distribution of loads generated by it and does not generate problems for the refrigerated chest structure. Thus, with the development of the air carrier, the task of transporting, loading, unloading and moving the bovine carcasses will be made easier, and with its installation in the refrigerated trunks, quality, functionality and ergonomics will be added to the tasks to be performed.